Phenotypic evaluation to define optimal sowing time for upland rice lines in the second crop in Campo das Vertentes region - Mulhanga, Arsénio Daniel Ivo; Garcia, Dionatas Alex; Berchembrock, Yasmin Vasques; Zevo, Ivan Natividade Júlio; Ferraz, Marcelo Araújo Junqueira; Botelho, Flávia Barbosa Silva (Acta Scientiarum. Agronomy, 2026)
Rice is a staple food for more than half of the world’s population. In Brazil, upland rice cultivation in the southeastern region faces competition from soybean due to its higher profitability in recent years. In this context, developing more competitive rice lines and expanding the sowing window, such as incorporating rice into the second season, can enhance its integration into cropping systems. This study aimed to evaluate the performance of elite upland rice lines under different sowing dates during the second crop season. Field experiments were conducted in Lavras, Minas Gerais State, Brazil, across 4 sowing dates in 7-day intervals, starting on January 28, 2022. Eight genotypes were evaluated in a randomized block design with a two-way factorial scheme (8 genotypes × 4 sowing dates). The assessed traits included the number of days to flowering (NDFL), plant height (PH), tolerance to Helminthosporium oryzae, and grain yield (GY). The data were analyzed using mixed models based on the restricted maximum likelihood/best linear unbiased predictor. The results revealed significant genetic variability for NDFL and PH as well as significant sowing date effects on NDFL, PH, and GY. A sharp decline in performance was observed across sowing dates, with an increase of 24 days in NDFL, a 14% reduction in PH, and sterility rates reaching 100% at the last sowing. These findings highlight the importance of genotype selection and optimal sowing timing to sustain upland rice production during the second crop season.